Assessing the impact of pesticides on pollinators - Maus, Christian (Burleigh Dodds Series in Agricultural Science, 2023)
This chapter provides an overview of the history of pollination biology, it begins by discussing the basics of pollination and goes on to discuss pollinators and their diversity. Sections also cover the ecology and evolution of floral traits, domestication and its impact on plant-pollinator relationships and how pollinators can impact agriculture. A section on modern agriculture and pollinators is also provided.